Stand-alone middle meningeal artery embolization in chronic subdural hematoma patient presenting cognitive decline: a case report - Galindra, Yusmahenry; Rilianto, Beny; Kurniawan, Ricky Gusanto; Prasetyo, Bambang Tri (Faculty of Medicine Universitas Indonesia, 2024)
Chronic subdural hematoma (cSDH) is a neurological disorder that commonly occurs in the elderly with high morbidity and mortality. Current treatment for cSDH consists of conservative therapy, surgical evacuation, and endovascular therapy, or a combination of all the methods. Endovascular therapy for cSDH management involving middle meningeal artery embolization (MMAE) has become a promising therapeutic option for clinicians as it offers a minimally invasive, safe, and effective choice with a low recurrence rate. MMAE using particles can also be performed in frail elderly patients who cannot undergo large craniotomy procedures. We presented a case of a subdural hematoma patient with cognitive decline using a therapeutic strategy of stand-alone MMAE, which resulted in cognitive function improvement